Need for recovery and physician well-being in emergency departments: national survey findings. (19th July 2021) - Cottey, Laura; Roberts, Tom; Graham, Blair; Horner, Daniel; Latour, Jos M.; Enki, Doyo; Lyttle, Mark D.; Stevens, Kara N.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and importance: Need for recovery (NFR) describes an individual's need to physically and psychologically recuperate following a period of work. Physicians working in emergency departments (EDs) have higher NFR scores than other occupational groups. Increased NFR may precede occupational burnout and identification provides opportunities for early interventions. Objective: To identify the incidence of well-being characteristics for ED physicians and to determine if NFR score is associated with these characteristics, whilst adjusting for potential confounders. Design: This is a secondary analysis of a survey study. Responses to 11 items were summated into the NFR score, from 0 (lowest NFR) to 100. Additional items ( n = 44) explored well-being, demographic and occupational characteristics. Setting and participants: Physicians working within 112 EDs in the UK and Ireland were surveyed in June–July 2019. Outcome measure and analysis: The outcome measure was self-perceptions of well-being including; current burnout, risk of future burnout and feeling overwhelmed at work. Descriptive statistics are presented alongside findings of a multiple regression analysis. Main results: In 4365 participants, the self-perceived incidence of current burnout, high risk of future burnout and feeling overwhelmed at work more than once a week was 24.8, 62.7 and 45.1%, respectively. For every unfavourable response of the NFR scale there was an increase in odds of 34.0% (95% CI, 31.0–37.1) for frequency of feeling overwhelmed; 53.8% (95% CI, 47.5–60.4) for current burnout; 56.2% (95% CI, 51.1–61.6) for high risk of future burnout. Conclusion: This study confirms an association between increased NFR score and self-perceived well-being characteristics. Factors previously reported to reduce NFR could therefore be important initiatives to improve well-being of the ED workforce.